(untitled) (Global Journal of Human-Social Science, 2018)
The paper discusses the challenges that confront cooperative relations between and among states on the issue of environment The environment has over the years remained a factor over which states relationship in the international system has been carried out both in cooperative manifestations and conflictive expressions As with many other issues the global environment represents a series of problems that are so complex and widespread that unilateral measures are not enough to forestall them Therefore relationships among states in the international system have been very active over the past decades in addressing many of the environmental problems In the concerted bid to rid the globe of environmental danger there had been international environmental conferences on climate change and other cooperative efforts to save the planet Notwithstanding the obvious successes that have been recorded by these cooperative efforts international environmental cooperation is still fraught with myriad of challenges Employing mainly the secondary method of data collection this paper analyzes the myriad challenges that confront international cooperative efforts to rid the globe of teething environmental problems